Strikingly diverse reactivity of structurally identical silylene and stannylene - Parvin, Nasrina; Dasgupta, Rajarshi; Pal, Shiv; Sen, Sakya S.; Khan, Shabana (Dalton Transactions, 2017)
The reactivity of structurally identical silylene and stannylene [PhC(NtBu)(2)EN(SiMe3)(2)] (E = Si (1) and Sn (2)) towards coinage metals has been explored. While 1 has the propensity to form an adduct with coinage metals (4 and 5), 2 undergoes a ligand exchange reaction with copper halides and silver triflate leading to PhC(NtBu) 2SnX (X = Br (6), Cl (7), and OSO2CF3 (8)) with concomitant formation of [M{N(SiMe3) (2)}] (M = Cu, Ag). However, with AgSbF6 both 1 and 2 led to ion pairs, 9(+) .SbF(6)(-)and 10(+) . SbF(6)(-)displaying weaker Ag center dot center dot center dot center dot F interactions in the latter.